Pengaruh Celebrity Endorsement Dan Online Customer Review Terhadap Loyalitas Merek Pada Brand Make Up Wardah Dengan Consumer Satisfaction Sebagai Variabel Mediasi - Aditya Dwi Hardianti; Rini Kuswati (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study probes the dynamics of Celebrity Endorsement, operationalized through Celebrity Influencer Credibility and Attractiveness, alongside Online Customer Review, on Brand Loyalty within the Wardah cosmetics product line, with Consumer Satisfaction functioning as a mediating variable. Adopting a quantitative-positivist paradigm, the survey was conducted on 100 purposive sampling respondents who had prior experience using Wardah products, followed national beauty influencers, and engaged with digital reviews. The instrument, an online questionnaire, was constructed from a synthesized set of indicators derived from theory and prior literature, and subsequently analyzed using Structural Equation Modeling (SEM) via Partial Least Squares (PLS). Findings indicate that Celebrity Influencer Credibility and Online Customer Review exert a positive and significant impact on consumer Attitude, whereas Attractiveness did not exhibit a statistically meaningful effect. Moreover, Attitude functions as a positive and significant catalyst for Consumer Satisfaction, which in turn stimulates Brand Loyalty. A direct effect of Attitude on Brand Loyalty was also observed, while Consumer Satisfaction acted as a partial mediator in this relationship. These results offer critical insights for influencer-based marketing strategies and e-WOM implementation in the cosmetic sector.